García Márquez : the man and his work - Bell-Villada, Gene H., 1941- (University of North Carolina Press, 1990)
Includes critical essays on such works as "One hundred years of solitude;" "The autumn of the patriarch;" "Chronicle of a death foretold;" and "Love in the time of cholera."